Leadership Styles and Their Influence on Employee Performance: Evidence from Nepalese Commercial Banks - Aryal, Narayan Prasad; Dipesh Khanal,; Gobind Kumar Singh,; Janga Bahadur Hamal, (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study aims to investigate the impact of leadership styles on employee performance within the Nepalese banking sector. Utilizing a quantitative research design, the study surveyed 400 employees from various commercial banks in Nepal. A structured questionnaire was employed to collect data, which was analyzed through descriptive and inferential statistics. The results shows that democratic leadership and commanding leadership have a positive and significant impact on the employee performance. On other hand, laissez- faire leadership has negative impacts on employee performance. This research contributes to the existing literature by providing empirical evidence between leadership styles and employee performance in the Nepalese banking context. It challenges previous findings that presented conflicting evidence regarding this relationship and offers a comprehensive framework for understanding how adaptive leadership can enhance organizational outcomes.